THE BIRD IN THE HAND FALLACY AND AGENCY PROBLEMS: A COMPARATIVE ANALYSIS - Shah, Binod; Sah, Kiran Kumari; Sah, Rajesh Kumar (PT. Antis International Publisher, 2024)
Through the conduction of comparative and comprehensive analysis of relevant data, literature review, and empirical evidence, this paper aims to apply to decision making and reasoning, the fallacy occurs when someone overvalues a sure thing, even when the potential benefits of an alternative option are significantly higher and more probable. Conversely, the agency problem, arising from conflicts of interest between managers and shareholders, can influence dividend decisions in ways that prioritize managerial interests over shareholder value maximization. The findings highlight significant influences of both the